Pengaruh Lokasi, Kualitas Pelayanan Dan Kualitas Produk Terhadap Keputusan Berkunjung Pada Caffe Ojuri - Rahman, Abd; Basalamah, Muhammad Ridwan; Wahono, Budi (UNIVERSITAS ISLAM MALANG, 2024)
Abstract This research aims to analyze the combined and individual influences of location, service quality, and product quality on consumer decisions to visit Caffe Ojuri. The study employs quantitative methods, gathering data through questionnaires distributed to consumers of Caffe Ojuri. The population comprises visitors to the café, and the sampling technique used is non-probability sampling. The sample size includes 87 respondents, and data were analyzed using descriptive statistics and multiple linear regression. The findings indicate that location, service quality, and product quality significantly influence consumers' decisions to visit Caffe Ojuri. Keywords: Location, Service Quality, Product Quality, Visiting Decision